2015
DOI: 10.5194/hess-19-2315-2015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying flood recharge and inter-aquifer connectivity using multiple isotopes in subtropical Australia

Abstract: Abstract. An understanding of hydrological processes is vital for the sustainable management of groundwater resources, especially in areas where an aquifer interacts with surface water systems or where aquifer interconnectivity occurs. This is particularly important in areas that are subjected to frequent drought/flood cycles, such as the Cressbrook Creek catchment in Southeast Queensland, Australia. In order to understand the hydrological response to flooding and to identify inter-aquifer connectivity, multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…This confirms observations from other studies (e.g. Baskaran et al, 2009;Hughes and Crawford, 2013;King et al, 2015), which also observed that high precipitation rainfall events associated with east coast pressure systems in Australia can be isotopically more depleted and less influenced by evaporation. The time series of hydraulic data indicates that recharge of both alluvial and MRV occurs following Table 3 Summary of bore data used in the temporal analysis of hydraulic head and river stage elevations.…”
Section: Stable Isotope Ratiossupporting
confidence: 91%
“…This confirms observations from other studies (e.g. Baskaran et al, 2009;Hughes and Crawford, 2013;King et al, 2015), which also observed that high precipitation rainfall events associated with east coast pressure systems in Australia can be isotopically more depleted and less influenced by evaporation. The time series of hydraulic data indicates that recharge of both alluvial and MRV occurs following Table 3 Summary of bore data used in the temporal analysis of hydraulic head and river stage elevations.…”
Section: Stable Isotope Ratiossupporting
confidence: 91%
“…Second, more abrupt depletions of 2 H and 18 O occurred during significant precipitation events (Fig. 2c), as has been reported in other parts of eastern Australia (Hughes and Crawford, 2013;King et al, 2015). In streamwater, isotopic ratios were generally lower for S1 and S2 than for rainfall, which most likely reflects the predominant contribution of depleted rainfall to recharge (Duvert et al, 2015b).…”
Section: Discussionmentioning
confidence: 55%
“…Since floods are considered as solely a surface phenomenon, there still is the risk of making incorrect predictions concerning flood development. It is important to understand that the river basin (with underlying aquifers) is a system with a complex balance, and changes in one part can cause significant changes in remote parts [11]. Not taking into account floods caused by tsunamis or tornadoes, the main traditionally declared factor of flood emergence and development remains precipitation.…”
Section: Introductionmentioning
confidence: 99%